Trajectories of Indonesian Adolescents' Religiosity, Problem Behavior, and Friends' Religiosity: Covariation and Sequences. Issue 4 (22nd February 2014) - French, Doran C.; Christ, Sharon; Lu, Ting; Purwono, Urip
<x xml:space="preserve">Abstract</x> Changes in religiosity, problem behavior, and their friends' religiosity over a 2‐year period were assessed in a sample of five hundred and fifty‐nine 15‐year‐old Indonesian Muslim adolescents. Adolescents self‐reported their religiosity, problem behavior, and friendships; the religiosity of mutual friends came from friends' self‐reports. A parallel process analysis of growth curves showed that adolescents' religiosity trajectories covaried with both problem behavior and friends' religiosity. Using a cross‐lagged model in which prior levels were controlled, religiosity at 10th and 11th grades predicted friends' religiosity 1 year later, suggesting that adolescents select friends of similar religiosity. This study provides evidence that religion is intertwined with other aspects of adolescent development and illustrates the importance of contextualizing adolescent religiosity within an ecological framework.